Comparison of the effectiveness of iranian sexual satisfaction training package and masters & johnson\'s approach on marital quality of married people - samirasadat rasouli; Mohsen Golparvar; mohammadarash ramezani; Jafar Hasani (مجله علوم روانشناختی, 2020)
Background: Marital quality can be considered the most important indicator of marital success that is influenced by various factors such as marital satisfaction, but the key question is which educational package has the most impact on the marital quality of couples? Aims: To compare the effectiveness of Iranian marital satisfaction training package and Masters & Johnson's approach on marital quality of couples. Method: The research design was quasi-experimental and the research design was three groups in three stages of pre-test, post-test and two months follow up. The statistical population consisted of 60 married individuals referring to two psychology and counseling centers in Tehran in the field of sexual relations in the winter of 1977. Were. The tools are: Demographic Fact Sheet and Marriage Quality Questionnaire of Busby, Crane, Larsen, & Christensen (1995), the Masters & Johnson Training Program (Masters & Johnson, 1976; quoted by Masters & Johnson & Claudia, 2006) and the Marital Satisfaction Training Package. Native Iranian (Rasouli, 1977). Data were analyzed by repeated measures ANOVA and post hoc test. Results: Native Iranian marital satisfaction training package and Masters & Johnson approach had significant effect on marital quality of couples (P<0/01). There was no significant difference between the two treatments in terms of marital quality (p<0/05). Conclusions: In order to increase the marital quality of couples, the Iranian marital satisfaction training package can be used.